Serum and Urinary Neutrophil Gelatinase-Associated Lipocalin Levels as Early Markers of the Renal Function in Patients With Urinary Stone-Induced Hydronephrosis - Xie, Tiancheng; Zhou, Hongmin; Gao, Yuchen; Xu, Xiao; Yao, Xudong; He, Xulin; Xu, Yunfei (Frontiers in Surgery, 2022)
Introduction: Urinary stones cause hydronephrosis, which leads to kidney function impairment. The serum creatinine level is frequently used as a marker of kidney function. However, in some patients with hydronephrosis, it does not reflect the kidney function changes in the early stages of kidney stone disease. Neutrophil gelatinase-associated lipocalin (NGAL) is a novel indicator of the kidney function. Previous NGAL-related research has focused on its role in acute kidney injury. This study aimed to determine the usefulness of NGAL as an early marker of the kidney function in patients with urinary stones and hydronephrosis. Methods: Eighty-five patients with urinary stones who were admitted to the Shanghai Tenth People’s Hospital (USP group) and 65 healthy volunteers (NC group) were recruited. Blood and urine samples collected from the study participants were evaluated using an enzyme-linked immunosorbent assay to determine the NGAL concentration. Data on the height, weight, age, medical history, and blood and urine findings were collected. Computed tomography data were collected from the USP group. Results: Compared to in the NC group, NGAL levels were significantly elevated in the USP group (P <0.001). However, no significant differences in the NGAL levels were observed among the USP group members with different degrees of hydronephrosis. Furthermore, no significant between-group differences in the creatinine level or the estimated glomerular filtration rate were observed. The areas under the receiver operating characteristic curves for the serum and urinary NGAL levels with hydronephrosis were 92.03% and 99.54%, respectively. The areas under the receiver operating characteristic curves for the serum and urinary NGAL levels with kidney stones were 85.05% and 91.89%, respectively. Conclusion: NGAL is a sensitive indicator of early kidney function changes secondary to urinary stones and hydronephrosis, and can predict kidney stone-induced hydronephrosis.